2015
DOI: 10.1093/toxsci/kfv194
|View full text |Cite
|
Sign up to set email alerts
|

N-(2-Aminoethyl) Ethanolamine-Induced Morphological, Biochemical, and Biophysical Alterations in Vascular Matrix Associated With Dissecting Aortic Aneurysm

Abstract: Dissecting aortic aneurysm (DAA) is an extended tear in the wall of the aorta along the plane of the vascular media. Our previous studies indicated in a developmental animal model, that DAA was related to pathological alteration in collagen, especially collagen type III. Accordingly, in the present studies, neonatal aortic vascular smooth muscle cells (VSMC) and timed pregnant Sprague-Dawley rat dams were treated with N-(2-aminoethyl) ethanolamine (AEEA), which, as shown previously, causes DAA in offspring. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 84 publications
(111 reference statements)
1
19
0
Order By: Relevance
“…45,51 Antibodies specific for p53, namely DO-1 (sc-126), Bp53-12 (sc-263), Pab240 (sc-99), C-19 (sc-1311-R), and FL393 (sc-6243), and antibodies against actin (sc-7210), PCNA (sc-56), and α-tubulin (sc-5546) were obtained from Santa Cruz Biotechnology, Inc (Dallas, TX). Amersham™ ECL™ Rainbow™ Marker (RPN800E, GE Healthcare Bio-Sciences, Pittsburgh, PA) was loaded in a lane in each gel and separated with the protein samples simultaneously as a reference for estimating the molecular weights of protein bands.…”
Section: Immunoblotsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,51 Antibodies specific for p53, namely DO-1 (sc-126), Bp53-12 (sc-263), Pab240 (sc-99), C-19 (sc-1311-R), and FL393 (sc-6243), and antibodies against actin (sc-7210), PCNA (sc-56), and α-tubulin (sc-5546) were obtained from Santa Cruz Biotechnology, Inc (Dallas, TX). Amersham™ ECL™ Rainbow™ Marker (RPN800E, GE Healthcare Bio-Sciences, Pittsburgh, PA) was loaded in a lane in each gel and separated with the protein samples simultaneously as a reference for estimating the molecular weights of protein bands.…”
Section: Immunoblotsmentioning
confidence: 99%
“…The polypeptides were transferred to polyvinylidene difluoride (PVDF) membranes (Bio-Rad Laboratories, Hercules, CA), as previously described. 45,51 Antibodies specific for p53, namely DO-1 (sc-126), Bp53-12 (sc-263), Pab240 (sc-99), C-19 (sc-1311-R), and FL393 (sc-6243), and antibodies against actin (sc-7210), PCNA (sc-56), and α-tubulin (sc-5546) were obtained from Santa Cruz Biotechnology, Inc (Dallas, TX). Antibody against calpain was a gift of Dr. R. L. Mellgren.…”
Section: Immunoblotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were cultured in Dulbecco's Modified Eagle’s Medium containing 4.5 g/L glucose, L-glutamine, and sodium pyruvate (catalog number 10-013-CV, Coming Life Sciences, Manassas, VA) and supplemented with 15% fetal calf serum (catalog # 10437028) and 1% 100 × Antibiotic-Antimycotic (catalog # 15240062) obtained from Gibco, Thermo Fisher Scientific (Waltham, MA). Cells were treated with AEEA as described previously (Chen et al, 2015). Sodium ascorbate (50 μg/ml), which is a crucial cofactor for lysyl oxidase, lysyl hydroxylase, and proline hydroxylase, was added daily for 5 days a week to stimulate ECM assembly (Pinnell, 1985; Pinnel et al, 1987; Davidson et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…AEEA induces aortic dissecting aneurysm in the offspring of rats exposed to the chemical during gestation (Moore et al, 2012; Schneider et al, 2012b). During studies of this developmental model of dissecting aortic aneurysm in the rat, our laboratory found that AEEA markedly alters the development of the extracellular matrix (ECM) both in vivo and in isolated rat aortic vascular smooth muscle cells in vitro (Xu et al, 2014; Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%